Scaled energy (z) distributions of charged hadrons observed in deep-inelastic muon scattering at 490 GeV from xenon and deuterium targets. - Adams, MR; Aïd, S; Anthony, P; Baker, MD; Bartlett, J; Bhatti, A; Braun, H; Busza, W; Carroll, T; Conrad, J; Coutrakon, G; Davisson, R; et al. (1994)
Fermilab Experiment-665 measured deep-inelastic scattering of 490 GeV muons off deuterium and xenon targets. Events were selected with a range of energy exchange from 100 GeV to 500 GeV and with large ranges of Q2 and xBj: 0.1 GeV2/c2